Desarrollo de una aplicación web para la predicción de riesgos cardiacos aplicando la tecnología de inteligencia artificial (Machine Learning)". - Reyes Toalumbo, Jazmin Lilibeth (2022)
The main objective of the web application at Vital Medical Clinic located in La Maná canton, El Carmen parish is to implement a web application to predict the cardiovascular events that affect the patients of the clinic with the use of artificial intelligence technology (Machine Learning), capturing the importance of the requirements in order to deliver a final software that accomplish all the expectations of the managing doctor. It is vital to choose design tools, development, and methodologies to achieve the expected success of the project, as well as to apply tests to verify the correct functioning of the web software. For this project, the RUP methodology has been used, because it is a disciplined methodology that seeks to solve the needs of the clients within the established time and budget. In addition, this methodology assigns tasks and responsibilities to the involved developers. In this way, the implementation of this web system has resolved the considered hypothesis for this project where the advantages of artificial intelligence technology has gained strength. All of this, thanks to the countless tools that these technologies use along with the results they produce. On the other hand, it is important to know specifically what is being resolved, how it is going to be applied, and principally, to keep to the schedule of activities of the established project to dismiss possible future complications that cause time to be wasted and consequently there is vulnerability of getting out of the established time.